BETAWI CULTURAL VILLAGE AS YOUNG GENERATION COLLABORATION SPACE TO PRESERVE JAKARTA - Astari, Safira (International Review of Humanities Studies, 2023)
illennials, Gen Z, and Post Gen Z residents are the majority in DKI Jakarta. Understanding their characteristics and behavior is the key to the success of preserving and developing Betawi culture. The purpose of this study is to examine the Betawi Cultural Village of Setu Babakan and the potential of Betawi culture in RW 9, Srengseng Sawah Village for the millennial generation. The methods used were library research with descriptive explorative approaches and field studies. The conclusion is: (1) Setu Babakan Betawi Cultural Village and its surroundings have various elements of Betawi culture so it should be a Betawi Culture storefront; (2) The COVID-19 pandemic situation emphasizes the need for the development and use of information technology for the preservation, maintenance, and development of cultural values as the identity and wealth of the people of DKI Jakarta; (3) Promotion of Betawi culture must be innovative, creative, fun and applicable through collaborative schemes based on digital technology so which enjoyed by the younger generation; (4) The government and the Betawi cultural community must have a strategic plan with a clear, firm and holistic roadmap.